Can The Competence of Village Apparatus and Community Participation Improve The Accountability of Village Fund Management? - Kardin, Ade Laely Fitriyani; Firmansyah, Amrie (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The village apparatus must be recognized as a legal community unit that has the right and power to regulate and manage village funds in order to improve development and community empowerment to achieve village welfare. This study aims to examine the competence and accountability of village officials and the community in managing village funds. This research is a type of quantitative research with an explanatory approach and uses primary data to distribute questionnaires online. Respondents in this study were 69 respondents using purpose sampling technique with the help of data analysis test using smart PLS software. The results of the study can be concluded that the competence of the village fund management apparatus and community participation have a positive effect on the accountability of village fund management.